Output power and efficiency in linear and ring configurations of continuous wave erbium doped fiber laser - Mat Yusoff, Rabi'atul Adawiyah (2017)
erbium doped fiber laser plays an important role in 1.5 micron wavelength region which contributes in many applications for example in communication such as erbium doped fiber amplifier and spectroscopy in medical fields. a continuous wave fiber laser operating at 1.5 micron wavelength region was demonstrated utilizing erbium doped as the gain medium in both linear and ring configurations. the output power and the efficiency of both linear and ring configurations of erbium doped fiber (edf) laser were characterised. the laser threshold and the efficiency of linear and ring configurations of edf laser then were compared. in the linear configuration, the wavelength division multiplexing (wdm) was used and fiber bragg gratings (fbgs) was inserting at both ends of the laser cavity. in the ring configuration, wdm and 3 db output coupler are used to complete the laser cavity. the slope efficiency for the linear configuration is 0.23 % while for the ring configuration is 2.12 %. the laser threshold where the lasing occurred for linear cavity is 88.8 mw and the laser threshold for ring cavity is 40.2 mw. the maximum output power for both linear and ring configurations are 0.32 mw and 4.13 mw respectively